Supplementation of culture medium with knockout serum replacement improves the survival of bovine secondary follicles when compared with other protein sources during in vitro culture. Issue 1 (11th October 2019) - Gomes, D.S.; Aragão, L.B.; Lima Neto, M.F.; Barroso, P.A.A.; Paulino, L.R.F.M.; Silva, B.R.; Souza, A.L.P.; Vasconcelos, G.L.; Silva, A.W.B.; Silva, J.R.V.
Summary: The present study evaluated the effect of knockout serum replacement (KSR), fetal bovine serum (FBS) and bovine serum albumin (BSA) on the viability and growth of bovine secondary follicles cultured in vitro for 12 days. To this end, secondary follicles were isolated (185–202 μm) and cultured in vitro in TCM-199 + medium supplemented with KSR (5% and 10%), FBS (5% and 10%) or BSA (3 mg/ml) at 38.5°C with 5% CO2 in air. Follicular diameters were evaluated on days 0, 4, 8 and 12. After 12 days of culture, follicular survival analysis was performing by using calcein-AM and ethidium homodimer. Before and after culture, follicles were fixed in paraformaldehyde for histological evaluation. Follicular diameter at different days of culture were compared using the Kruskal–Wallis test, while the percentages of viable follicles were analyzed by chi-squared test ( P < 0.05). Results showed that follicles cultured in the presence of KSR at both concentrations presented higher follicular survival rates than those cultured in control medium alone or supplemented with FBS or BSA. Conversely, the presence of KSR, BSA or FBS did not increase follicular diameter after 12 days of culture. Histology analysis showed that, among the tested treatments, follicles cultured in the presence of KSR had preserved rounded oocytes, juxtaposed granulosa cells and intact basal membrane. In conclusion, supplementation of culture medium with KSR increases the follicular survival of bovine secondary follicles cultured in vitro .